Challenges in “probing spectroscopic probes” for noninvasive simultaneous disease diagnosis - Lopamudra Roy; Shweta Paul; Amrita Banerjee; Ria Ghosh; Susmita Mondal; Monojit Das; Monojit Das; Nivedita Pan; Ishitri Das; Soumendra Singh; Debasish Bhattacharya; Asim Kumar Mallick; et al. (Frontiers in Chemistry)
Noninvasive diagnosis of human diseases relies on the detection of molecular markers (probes) in a painless manner. Although extrinsic and intrinsic molecular markers are often used, intrinsic disease probes (molecular markers) are preferable because they are naturally present in our body, and deviation in their concentration from normal levels clearly indicates anomalies in human bodies, that is, diseases. In this study, we report noninvasive spectroscopic measurements of total haemoglobin (Hb), bilirubin, and the ratio of oxy- and deoxyhaemoglobin as disease markers for anaemia, jaundice, and oxygen deficiency, respectively, using a meticulously designed optical fibre probe. The challenges in designing the fibre probe for simultaneous noninvasive detection, including optical power, spectral density of the probing light, and resolution of the spectrometer, were found to be critical to accurate measurements. Finally, a fibre-less, highly portable, and low-cost prototype was developed and tested in human clinical trials for the diagnosis of diseases, and these results were compared with conventional techniques (blood tests).